The moderating role of transformational leadership on HR practices in M&A integration. Issue 20 (12th November 2016) - Vasilaki, Athina; Tarba, Shlomo; Ahammad, Mohammad Faisal; Glaister, Alison J.
Abstract : Scant research exists examining the effect of HRM practices on employee behavior in Merger and acquisition (M&A) integration and the role that leaders play within this. This paper develops a conceptual framework that focuses on the moderating role of transformational leadership on the achievement of human integration and organizational identification in M&A integration. We argue that communication, employee involvement, teamwork, and training and development have a positive effect on employee behavior and their identification with the newly formed organization. Moreover, we argue that transformational leadership behaviors will moderate the implementation of HRM practices in M&As, leading to positive employee behavior and employee identification in the new organization. We suggest that further research is necessary to test propositions of the present study in order to achieve finer-grained understanding of the role of transformational leadership on the achievement of human integration and organizational identification in M&A integration.